2009
DOI: 10.1186/1471-2164-10-102
|View full text |Cite
|
Sign up to set email alerts
|

A gene-rich linkage map in the dioecious species Actinidia chinensis (kiwifruit) reveals putative X/Y sex-determining chromosomes

Abstract: BackgroundThe genus Actinidia (kiwifruit) consists of woody, scrambling vines, native to China, and only recently propagated as a commercial crop. All species described are dioecious, but the genetic mechanism for sex-determination is unknown, as is the genetic basis for many of the cluster of characteristics making up the unique fruit. It is, however, an important crop in the New Zealand economy, and a classical breeding program would benefit greatly by knowledge of the trait alleles carried by both female an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 55 publications
3
77
0
2
Order By: Relevance
“…This population was used in the recently developed Actinidia linkage map (Fraser et al, 2009), and preliminary data indicated that CP activity segregated within this population (data not shown). As all Actinidia species are functionally dioecious, CP activity measurements could only be made on fruit from the females (n = 133) in the mapping population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This population was used in the recently developed Actinidia linkage map (Fraser et al, 2009), and preliminary data indicated that CP activity segregated within this population (data not shown). As all Actinidia species are functionally dioecious, CP activity measurements could only be made on fruit from the females (n = 133) in the mapping population.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, together with the desire to understand the function of actinidin in planta, we have targeted the nature of CP variation in kiwifruit for study. In this paper, we utilize a gene-rich linkage map in A. chinensis (Fraser et al, 2009) to identify a major quantitative trait locus (QTL) for CP activity and show that it colocates with the gene encoding the major acidic isoform of actinidin. Complementation of ACT1A mutations in transgenic YellowA fruit allowed the physiological consequences of increased CP activity in fruit to be investigated.…”
mentioning
confidence: 99%
“…The maps were produced with LOD scores ≥2 (as an indication of coinheritance of loci). Continued progress in Actinidia mapping led to a significant advancement in Actinidia genetics, with the generation of a gene-rich linkage map of A. chinensis, constructed using 644 SSRs, and defining the 29 chromosomes of the haploid genome (Fraser et al, 2009). Again, SSRs were the marker of choice, owing to their abundance, distribution in coding and non-coding regions, reproducibility, Mendelian mode of inheritance and co-dominant nature.…”
Section: Molecular Markers and Mappingmentioning
confidence: 99%
“…9 This system of reproduction is linked to an active Y sex chromosome system (XX/XY female/male) proposed to be in the early stages of evolution. 10 In their natural habitats in south-western China, A. deliciosa flowers are pollinated by a large array of insects, mainly bees, including honey bees, carpenter bees, smaller native bees and bumble bees, but other insects such as hoverflies have also been implicated. 11 In A. polygama it was shown that the major flower visitors were bumble bees, small solitary bees and hoverflies.…”
Section: Evolution Of Terpene Synthasesmentioning
confidence: 99%